Meta-analysis of dengue vaccine effectiveness - Pardomuan Robinson Sihombing (Privietlab, 2025)
Dengue hemorrhagic fever has a staggering 390 million cases to date and was the predominant virus in 128 countries in 2022. This study aims to determine vaccination safety and response with respect to negative endpoints over time in the cohort. A systematic review and meta-analysis was performed according to the 2020 PRISMA statement. Comprehensive searches were performed for primary open-access articles in the PubMed and Scopus databases from years 2013-2023. Statistical analysis used random effect modelling a pooled relative risk would be calculated for the efficacy of the vaccine using proportional difference methodology, with 960 articles retrieved (10 articles meeting inclusion criteria incorporated 157,345 study participants) data was arrived in a 2023 publication whereby. The findings were as follows: the tetravalent dengue vaccine had an overall pooled efficacy of 64.6% (95% CI 47.4%-76.2%) and I² 94.7%, with TAK-003 being more efficacious (76.8%, 95% CI 60.8%-86.2%) than CYD-TDV (53.6%, 95% CI 28.9%-69.7%) in symptomatic dengue. The dengue vaccine showed promising efficacy and satisfactory immune response, with TAK-003 showing more consistent performance than CYD-TDV, especially in the absence of heterogeneity between studies. Implications: These findings support the implementation of dengue vaccination with preference for the TAK-003 platform, demonstrating better efficacy consistency to maximize benefits and minimize risk..